2012
DOI: 10.4161/cc.20811
|View full text |Cite
|
Sign up to set email alerts
|

Repression of endometrial tumor growth by targeting SREBP1 and lipogenesis

Abstract: The aberrantly increased lipogenesis is a universal metabolic feature of proliferating tumor cells. Although most normal cells acquire the bulk of their fatty acids from circulation, tumor cells synthesize more than 90% of required lipids de novo. The sterol regulatory element-binding protein 1 (SREBP1), encoded by SREBF1 gene, is a master regulator of lipogenic gene expression. SREBP1 and its target genes are overexpressed in a variety of cancers; however, the role of SREBP1 in endometrial cancer is largely u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
66
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 64 publications
(70 citation statements)
references
References 51 publications
(56 reference statements)
4
66
0
Order By: Relevance
“…Among the transcriptional activators of lipogenic genes, SREBP-1a is highly expressed in many cancer cell-lines and multiple types of cancer, including endometrial cancer, colorectal cancer and pancreatic cancer (11,26,27). The SREBP-1a level is also correlated with cancer progression and metastasis (28,29).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the transcriptional activators of lipogenic genes, SREBP-1a is highly expressed in many cancer cell-lines and multiple types of cancer, including endometrial cancer, colorectal cancer and pancreatic cancer (11,26,27). The SREBP-1a level is also correlated with cancer progression and metastasis (28,29).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, SREBP-1a is a potent transcriptional activator for all known SREBP-target genes (7). The SREBP1 protein levels are often correlated with tumor size, histological grade and metastasis, and SREBP1 loss of function inhibits cell proliferation and induces apoptosis, cell migration and invasion in liver, ovarian and endometrial cancers (8)(9)(10)(11). Furthermore, genetic depletion or pharmacological inhibition of SREBP1 has been shown to suppress the epidermal growth factor receptor (EGFR)-induced glioblastoma (12).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, we established that SIRT1 positively regulates SREBP1 in EC. Our previous study showed that overexpression of SREBP1 was found in EC and it promoted tumor cell proliferation and tumor growth (16), and since the inhibition of SIRT1 can lower the expression of SREBP1, it can suppress tumor growth and progression. We further studied the role of SIRT1 in tumor growth in the following experiment.…”
Section: Effect On Srebp1 With the Silencing Of Sirt1 In Rl95-2 Cell mentioning
confidence: 99%
“…In our previous studies, we demonstrated that SREBP1 is overexpressed in endometrial and ovarian cancer and the expression of SREBP1 protein increased with higher FIGO surgical stage and histological grade of the disease. Furthermore, knockdown of SREBP1 could induce apoptosis, reduce cell proliferation in vitro and in vivo (16,17 …”
mentioning
confidence: 99%